Triglyceride-Glucose Index in Parotid Gland Tumours: A Novel Biomarker for Differentiating Warthin Tumour and Pleomorphic Adenoma - DOĞAN R.; KÜÇÜK R. B.; YENİGÜN A.; DOĞAN E. E.; ÖZTURAN O. (My University, 2026)
Introduction: Pleomorphic adenoma and Warthin tumour are the two most common benign parotid gland tumours with distinct histological and clinical profiles. Recent studies suggest a potential link between metabolic disturbances-particularly insulin resistance-and the development of Warthin tumours. The triglyceride-glucose (TyG) index has emerged as a simple, cost-effective biomarker of insulin resistance. This study aimed to investigate the potential role of the TyG index in differentiating between pleomorphic adenoma and Warthin tumour. Methods: A retrospective cross-sectional study was conducted on patients histopathologically diagnosed with pleomorphic adenoma (n = 31) or Warthin tumour (n = 22), and compared with healthy controls (n = 58). Fasting glucose and triglyceride levels were used to calculate the TyG index. Statistical analyses included t-tests, ANOVA, and Bonferroni-corrected post hoc comparisons, with a significance threshold of p < 0.05. Results: No significant differences were observed in age, sex, BMI or TyG index between the tumour group and controls. However, the TyG index was significantly higher in the Warthin tumour group (4.91 +/- 0.28) compared to the pleomorphic adenoma (4.68 +/- 0.31, p = 0.006) and control groups (4.72 +/- 0.23, p = 0.033). No difference was found between the pleomorphic adenoma and control groups. Conclusion: The TyG index is significantly elevated in patients with Warthin tumours, supporting its potential role as a simple, non-invasive biomarker to aid in the differential diagnosis of benign parotid tumours.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp; Klinik Tıp (Med); Otorhinolaryngology; Clinical Medicine; Clinical Medicine (Med); Konuşma ve İşitme; Speech and Hearing